Ventricular Tachycardia Precipitated by Short-long-short Sequence in a Patient with Implantable-cardioverter Defibrillator - Diego Chemello, MD; Anandaraja Subramanian, MD; Sheila Watkins, RN; Douglas Cameron, MD FRCPC (Indian Pacing and Electrophysiology Journal, 2012)
Abrupt changes in heart rate, particularly short-long-short sequences in the ventricular cycle length (CL), might precede initiation of ventricular tachycardia/fibrillation (VT/VF). These changes may be facilitated or caused by pacing activity in patients with pacemakers or implantable-cardioverter defibrillators (ICDs). We describe a patient with two episodes of acquired VT precipitated by short-long-short sequences and diagnosed from the ICD recordings. In such cases, the knowledge of the device parameters is extremely important for a correct diagnosis and management.